Multisensory speech enhancement using lower‐frequency components from bone‐conducted speech. Issue 11 (25th July 2019) - Rahman, M. Shahidur; Saha, Atanu; Shimamura, Tetsuya
Abstract: In this article, we present a multisensory speech enhancement technique by suppressing low‐frequency band noise from the speech signal. Speech is often corrupted by color noises like car and multi‐talker babble noise that affect mostly the low‐frequency region of the speech signal. We propose a multisensory approach for noise reduction by utilizing bone‐conducted (BC) speech. Since BC speech is caused by the vibrations that travel through the vocal tract wall and skull bone, it is robust against ambient conditions. Unfortunately, BC speech suffers from intelligibility because it lacks higher‐frequency components. However, the low‐frequency region of BC speech is completely intelligible. When the normal air‐conducted (AC) speech gets corrupted by low‐frequency band noise, it can be readily suppressed by replacing the low‐frequency region of noisy AC speech with that of BC speech. Because the proposed method does not require any noise estimation, it is thus possible to avoid distortion introduced due to imperfect noise estimation by the traditional enhancement techniques. Evaluation results show that the method can be effectively used for suppressing low‐frequency band noise even under very low signal to noise ratio (SNR) conditions. © 2019 Institute of Electrical Engineers of Japan. Published by John Wiley & Sons, Inc.